Cost reduction and optimization in gerbera micropropagation replacing potassium nitrate for a commercial fertilizer in the culture medium - Cinthia Carolinne de Souza Ferreira; Cristiane Domingos da Paz; Joselita Cardoso de Souza; Ana Rosa Peixoto; Alessandro Rosa Nascimento; Juliana Martins Ribeiro; Silvio Lopes Teixeira; Lucas Silva Rios (Acta Scientiarum: Biological Sciences)
Due to profuse bureaucracy and high costs of high purity potassium nitrate (KNO3), we intend to check the possibility of replacing this reagent with a similar commercial mineral fertilizer that costs less and is easier to procure. The experiment consisted of seven treatments with the fertilizer Dripsol® NKS, replacing the high purity potassium nitrate (KNO3 PA) in the culture medium for rooting gerbera. The control treatment (T1) consisted of inorganic MS salts, containing 1.9 g L-1 KNO3 PA and, in the other treatments, the KNO3 of the MS medium was replaced by the fertilizer in the following concentrations (g L-1): T2 0; T3; 0,5; T4; 1,0; T5; 1,5; T6; 2,0 e T7; 2.5. In the rooting phase, after 35 days in the growing room, the average length of the root, the average length of the aerial part, the number of leaves, and the fresh biomass average value of the hybrid Gerbera DTCS were evaluated. Fertilizer at a concentration of 0.5 g L-1 generated results equal to or greater than those of the control treatment for all variables analyzed in vitro conditions. In the ex vitro experiment, seedlings from the in vitro cultivation with commercial fertilizer were acclimated and later transplanted to a vivarium where their development was monitored until flowering. In this experiment, the average root length, average number of roots, average length of the aerial part, number of leaves, leaf area, fresh biomass average value, and absorption of macronutrients (during the vegetative phase) were assessed. No morphological changes were observed. In view of the results, it was possible to prove the feasibility of replacing KNO3 (PA) for the commercial NKS® fertilizer in the preparation of the culture medium for in vitro propagation of gerbera, in a smaller rate, thus reducing approximately 97.0% of costs and eliminating bureaucratic obstacles applicable to the procurement of KNO3.